Enhancing Mass and Yield Product of Propylene Glycol Production through Glycerol Hydrogenolysis - Arifin, Dhea Wahyu Amanda; Firdaus, Luthfi Maulana; Huda, Muhammad Danil; Abdat, Muhammad Saefillahil; Indriani, Navira Amalia (Journal of Chemical Engineering Research Progress, 2024)
The chemical industry in Indonesia continues to experience significant growth in both innovation and technology. One of the significant areas of improvement is in supporting materials, exemplified by propylene glycol. The process of producing propylene glycol from glycerol involves hydrogenolysis. The hydrogenolysis process of propylene glycol is the reaction of glycerol with hydrogen gas under specific conditions. The effects of process innovation or modification with the aim of enhancing mass efficiency and yield of propylene glycol. Methods to increase mass efficiency and yield using the Aspen HYSYS V11 simulator tool and implemented effectively. From the process modifications that have been implemented, it can be concluded that this design is quite effective as it mass and yields more efficiency, with one notable improvement being mass efficiency of propylene glycol from 7304 ton/year to 10012 ton/year and the percentage yield of propylene glycol in the final product increasing from 70% to 98%. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).